Electromagnetic wave shielding material, electronic component, and electronic apparatus

By using a multi-layer structure with magnetic layers sandwiched between two metal layers in electromagnetic wave shielding material, the problem of degradation of shielding performance of existing materials at high temperatures is solved, and the effect of maintaining high shielding performance at high temperatures is achieved. .

CN119487986APending Publication Date: 2025-02-18FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380049793.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult to maintain high shielding performance after existing electromagnetic wave shielding materials are placed at high temperatures.

Method used

The electromagnetic wave shielding material is used to sandwich a magnetic layer containing magnetic particles and resin between two metal layers. The loss tangent Tanδ under the dynamic viscoelasticity measurement of 1 Hz is smaller than that of 0°C to 70°C. 0.35.

Benefits of technology

This material can maintain high electromagnetic wave shielding performance at high temperatures and is suitable for electronic parts and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208578830000291
    Figure BDA0005208578830000291
Patent Text Reader

Abstract

The present invention provides an electromagnetic wave shielding material having a magnetic layer containing magnetic particles and a resin between two metal layers, and an electronic component and an electronic device comprising the electromagnetic wave shielding material, and the loss tangent (Tan [delta]) of the magnetic layer in a dynamic viscoelasticity measurement at 1 Hz is less than 0.35 in a temperature range of 0 DEG C to 70 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electromagnetic wave shielding material, an electronic component and an electronic device. Background Art

[0002] Patent Document 1 discloses a soft magnetic film mounted on a circuit board of an electronic device. Specifically, paragraph 0095 of Patent Document 1 describes that a soft magnetic film can be laminated on an antenna, a coil, or a circuit board having an antenna or a coil formed on its surface.

[0003] Previous technical literature

[0004] Patent Literature

[0005] Patent document 1: WO2014 / 132880 Summary of the invention

[0006] Technical issues to be solved by the invention

[0007] In recent years, electromagnetic wave shielding materials have attracted attention as materials for reducing the influence of electromagnetic waves in various electronic parts and various electronic devices. Electromagnetic wave shielding materials (hereinafter, also recorded as "shielding materials") can play a role in shielding electromagnetic waves (hereinafter, also recorded as "electromagnetic wave shielding performance" or "shielding performance") by making the electromagnetic waves incident on the shielding materials reflected by the shielding materials and / or attenuated inside the shielding materials. For example, the soft magnetic film described in Patent Document 1 can play a role as an electromagnetic wave shielding material.

[0008] Electromagnetic wave shielding materials are required to have high shielding performance. Electromagnetic wave shielding materials that have high shielding performance against electromagnetic waves can help to significantly reduce the impact of electromagnetic waves in electronic parts and electronic devices. However, the results of the inventor's research have shown that it is difficult for conventional electromagnetic wave shielding materials to have high shielding performance after being placed at high temperatures.

[0009] An object of one embodiment of the present invention is to provide an electromagnetic wave shielding material that can exhibit high shielding performance even after being left at high temperatures.

[0010] Means for solving technical problems

[0011] One embodiment of the present invention is as follows.

[0012] [1] An electromagnetic wave shielding material having a magnetic layer containing magnetic particles and a resin between two metal layers, and

[0013] The magnetic layer has a loss tangent Tanδ of less than 0.35 in a temperature range of 0°C to 70°C in a 1 Hz dynamic viscoelasticity measurement.

[0014] [2] The electromagnetic wave shielding material according to [1], wherein

[0015] The magnetic layer contains a resin containing a urethane bond.

[0016] [3] The electromagnetic wave shielding material according to [1] or [2], wherein

[0017] The glass transition temperature of the resin is -60°C or higher and lower than 0°C.

[0018] [4] The electromagnetic wave shielding material according to any one of [1] to [3], wherein

[0019] The magnetic layer contains a urethane bond-containing resin having a glass transition temperature of -60°C or higher and lower than 0°C.

[0020] [5] The electromagnetic wave shielding material according to any one of [1] to [4], wherein

[0021] The magnetic layer contains polyfunctional isocyanate.

[0022] [6] The electromagnetic wave shielding material according to any one of [1] to [5], wherein

[0023] The magnetic layer contains 15 parts by mass or more of the polyfunctional isocyanate based on 100 parts by mass of the resin.

[0024] [7] The electromagnetic wave shielding material according to any one of [1] to [6], wherein

[0025] The magnetic layer has a magnetic permeability of 100 or more.

[0026] [8] An electromagnetic wave shielding material according to any one of [1] to [7], comprising two or more multilayer structures, wherein the multilayer structure has a magnetic layer between two metal layers, wherein the loss tangent Tanδ under 1 Hz dynamic viscoelasticity measurement is less than 0.35 in the temperature range of 0°C to 70°C.

[0027] [9] The electromagnetic wave shielding material according to [1], wherein

[0028] The magnetic layer contains a urethane bond-containing resin having a glass transition temperature of not less than -60°C and less than 0°C.

[0029] The magnetic layer contains 15 parts by mass or more of a polyfunctional isocyanate when the content of the resin is 100 parts by mass.

[0030] The magnetic permeability of the magnetic layer is greater than 100, and

[0031] The electromagnetic wave shielding material includes two or more multilayer structures, and the multilayer structure has a magnetic layer between two metal layers, whose loss tangent Tanδ under 1 Hz dynamic viscoelasticity measurement is less than 0.35 in the temperature range of 0°C to 70°C.

[0032]

[10] An electronic component comprising the electromagnetic wave shielding material according to any one of [1] to [9].

[0033]

[11] An electronic device comprising the electromagnetic wave shielding material according to any one of [1] to [9].

[0034] Effects of the Invention

[0035] According to one aspect of the present invention, an electromagnetic shielding material that can exhibit high shielding performance even after being left at high temperature can be provided. In addition, according to one aspect of the present invention, an electronic component and an electronic device including the electromagnetic shielding material can be provided. DETAILED DESCRIPTION

[0036] [Electromagnetic wave shielding materials]

[0037] One embodiment of the present invention relates to an electromagnetic wave shielding material having a magnetic layer containing magnetic particles and a resin between two metal layers, wherein the loss tangent Tanδ of the magnetic layer in a 1 Hz dynamic viscoelasticity measurement is less than 0.35 in a temperature range of 0°C to 70°C.

[0038] In the present invention and this specification, "electromagnetic wave shielding material" refers to a material that can show shielding performance against electromagnetic waves of at least one frequency or at least a part of the frequency band. "Electromagnetic waves" include magnetic field waves and electric field waves. "Electromagnetic wave shielding material" is preferably a material that can show shielding performance against one or both of magnetic field waves of at least one frequency or at least a part of the frequency band and electric field waves of at least one frequency or at least a part of the frequency band.

[0039] In the present invention and this specification, "magnetism" refers to ferromagnetism (ferromagnetic property). The magnetic layer will be described in detail later.

[0040] In the present invention and this specification, "metal layer" refers to a layer containing metal. The metal layer may be a layer containing one or more metals, and the one or more metals may be a pure metal composed of a single metal element, an alloy of two or more metal elements, or an alloy of one or more metal elements and one or more non-metal elements. The metal layer will be described in detail later.

[0041] <Tanδ of magnetic layer>

[0042] In the electromagnetic wave shielding material, the loss tangent Tanδ of the magnetic layer located between the two metal layers under the dynamic viscoelasticity measurement at 1 Hz is less than 0.35 in the temperature range of 0°C to 70°C. "Tan" is an abbreviation of Tangent. In the present invention and this specification, the loss tangent Tanδ (tangent δ) is obtained by the dynamic viscoelasticity measurement described below.

[0043] The dynamic viscoelasticity measurement is performed using a dynamic viscoelasticity measuring device. As the dynamic viscoelasticity measuring device, for example, a dynamic viscoelasticity measuring device DMS6100 manufactured by Hitachi High-Tech Science Corporation can be used, and this device is used in the Examples described below.

[0044] The assay steps are as follows.

[0045] A measurement sample of 28 mm × 10 mm size is cut out from the magnetic layer of the measurement object. Regarding the measurement sample, for example, the measurement sample can be cut out from the magnetic layer used to make the electromagnetic wave shielding material. Alternatively, the magnetic layer can be taken out from the manufactured electromagnetic wave shielding material by a known method, and the measurement sample can be cut out from the taken out magnetic layer. This is also the same for the measurement sample used for various measurements related to the magnetic layer.

[0046] In a dynamic viscoelasticity measuring device, the viscoelasticity of the above-mentioned sample for measurement is measured under the following measurement conditions. The above-mentioned "loss tangent Tanδ in the dynamic viscoelasticity measurement at 1 Hz is less than 0.35 in the temperature range of 0°C to 70°C" means that the maximum value of the loss tangent Tanδ in the data in the temperature range of 0°C to 70°C measured in this way is less than 0.35.

[0047] (Measurement conditions)

[0048] Chuck spacing: 10mm

[0049] Measuring temperature range: -50℃ to 100℃

[0050] Heating rate: 2℃ / min

[0051] Sampling rate: 3 seconds

[0052] Measuring frequency: 1Hz

[0053] Regarding the above-mentioned electromagnetic wave shielding material, the inventor speculates that the reason why the above-mentioned electromagnetic wave shielding material can exert high shielding performance against electromagnetic waves is that the above-mentioned electromagnetic wave shielding material has a multilayer structure with a magnetic layer sandwiched between two metal layers. The details are as follows. In order to obtain high shielding performance against electromagnetic waves in the electromagnetic wave shielding material, it is preferred to increase the reflection at the interface in addition to improving the attenuation ability of electromagnetic waves. That is, it is preferred that the electromagnetic wave is greatly attenuated by repeatedly reflecting at the interface and passing through the shielding material many times. However, as for the behavior of the metal layer and the magnetic layer to electromagnetic waves, the metal layer has a tendency that the attenuation ability of electromagnetic waves is large but the reflection of the magnetic field wave at the interface is small, and the magnetic layer has a tendency that the attenuation ability of electromagnetic waves is smaller than that of the metal layer but the reflection of the magnetic field wave at the interface is greater than that of the metal layer. Therefore, it is not easy to take into account both high reflection and attenuation for electromagnetic waves, especially magnetic field waves, by relying solely on the metal layer or the magnetic layer. In contrast, the above-mentioned electromagnetic wave shielding material can take into account both the reflection at the interface and the attenuation within the layer by including a multilayer structure with a magnetic layer between two metal layers. The inventor believes that this is the reason why the above-mentioned electromagnetic wave shielding material can exert high shielding performance against magnetic field waves. However, the present invention is not limited to the speculation described in this specification.

[0054] In addition, the loss tangent Tanδ of the magnetic layer sandwiched between the two metal layers under the 1 Hz dynamic viscoelasticity measurement is less than 0.35 in the temperature range of 0°C to 70°C, and the inventors believe that this contributes to the improvement of the heat resistance of the shielding performance of the above-mentioned electromagnetic wave shielding material. The inventors speculate that as a result, the above-mentioned electromagnetic wave shielding material can also exhibit high shielding performance after being left at high temperatures.

[0055] From the viewpoint that the electromagnetic wave shielding material can exert high shielding performance even after being placed at high temperature by suppressing the decrease in shielding performance after being placed at high temperature, the loss tangent Tanδ of the magnetic layer under the dynamic viscoelasticity measurement of 1 Hz is less than 0.35 in the temperature range of 0°C to 70°C. That is, in the temperature range of 0°C to 70°C, the maximum value of the loss tangent Tanδ of the magnetic layer under the dynamic viscoelasticity measurement of 1 Hz is less than 0.35. From the viewpoint of further suppressing the decrease in shielding performance after being placed at high temperature, the maximum value is preferably 0.34 or less, and more preferably 0.32 or less, 0.30 or less, 0.28 or less, 0.25 or less, 0.23 or less, 0.20 or less, and 0.18 or less in sequence. The maximum value may be, for example, 0.05 or more, 0.07 or more, 0.10 or more, or 0.12 or more. However, from the viewpoint of suppressing the decrease in shielding performance after being placed at high temperature, the maximum value is preferably small, so the maximum value may also be smaller than the value exemplified here. On the other hand, the minimum value of the loss tangent Tanδ of the magnetic layer in the 1 Hz dynamic viscoelasticity measurement within the temperature range of 0°C to 70°C is not particularly limited, and may be, for example, greater than 0, 0.01 or more, or 0.02 or more.

[0056] Tan δ of the magnetic layer can be controlled by the type and content of the components contained in the magnetic layer, etc. This will be described in detail later.

[0057] Hereinafter, the above-mentioned electromagnetic wave shielding material will be described in further detail.

[0058] <Magnetic layer>

[0059] The magnetic layer contains magnetic particles and resin.

[0060] (Magnetic Particles)

[0061] As magnetic particles, one selected from the group consisting of magnetic particles generally referred to as soft magnetic particles, such as metal particles and ferrite particles, or a combination of two or more can be used. Metal particles generally have a saturation magnetic flux density of about 2 to 3 times that of ferrite particles, so they will not be magnetically saturated even in a strong magnetic field and maintain relative magnetic permeability to show shielding performance. Therefore, the magnetic particles contained in the magnetic layer are preferably metal particles. In the present invention and this specification, the layer containing metal particles as magnetic particles belongs to the "magnetic layer".

[0062] Metal particles

[0063] As metal particles of the above-mentioned magnetic particles, for example, particles such as sendust (Fe-Si-Al alloy), permalloy (Fe-Ni alloy), molybdenum permalloy (Fe-Ni-Mo alloy), Fe-Si alloy, Fe-Cr alloy, Fe-containing alloy commonly known as iron-based amorphous alloy, Co-containing alloy commonly known as cobalt-based amorphous alloy, alloy commonly known as nanocrystalline alloy, iron, permendur (Fe-Co alloy) can be cited. Among them, sendust shows high saturation magnetic flux density and relative magnetic permeability, so it is preferred. In addition to containing the constituent elements of the metal (including alloy), the metal particles can also contain elements contained in additives that can be added arbitrarily and / or elements contained in impurities that may be accidentally mixed in the manufacturing process of the metal particles at any content rate. The content rate of the constituent elements of the metal (including alloy) in the metal particles is preferably 90.0 mass% or more, more preferably 95.0 mass% or more, and can be 100 mass%, less than 100 mass%, 99.9 mass% or less, or 99.0 mass% or less.

[0064] In one embodiment, the shielding performance of an electromagnetic wave shielding material against electromagnetic waves can be evaluated using the magnetic permeability (specifically, the real part of the complex relative magnetic permeability) of a magnetic layer contained in the electromagnetic wave shielding material as an indicator. An electromagnetic wave shielding material having a magnetic layer showing high magnetic permeability (specifically, the real part of the complex relative magnetic permeability) can exhibit high shielding performance against electromagnetic waves and is therefore preferred.

[0065] When the complex relative magnetic permeability is measured by a magnetic permeability measuring device, the real part μ' and the imaginary part μ" are usually displayed. The "magnetic permeability" in the present invention and this specification refers to the real part μ'. Hereinafter, the real part of the complex relative magnetic permeability at a frequency of 3 MHz (megahertz) is also referred to as "magnetic permeability" or "magnetic permeability μ'". The magnetic permeability can be measured by a commercially available magnetic permeability measuring device or a magnetic permeability measuring device of a known structure. The measuring temperature is set to 25°C. By setting the ambient temperature of the measuring sample to the measuring temperature, the temperature of the measuring sample can be set to the measuring temperature due to the establishment of temperature equilibrium. From the viewpoint of being able to exert a more excellent electromagnetic wave shielding performance, the magnetic The magnetic permeability of the layer (real part of the complex relative magnetic permeability at a frequency of 3 MHz) is, for example, greater than 40, preferably greater than 100, and more preferably greater than 120. Furthermore, the above-mentioned magnetic permeability may be, for example, less than 500, less than 300, or less than 200, and may be higher than the value exemplified here. The electromagnetic wave shielding material having a high magnetic permeability is preferred because it can exhibit excellent electromagnetic wave shielding performance. The above-mentioned magnetic permeability may be a value obtained for the magnetic layer before being placed at a high temperature of 60°C or above (however, excluding the heating process in the manufacturing process of the magnetic layer and the electromagnetic wave shielding material, the same below). Furthermore, the above-mentioned magnetic layer can also show a magnetic permeability in the above-mentioned range after being placed at a high temperature of 60°C or above.

[0066] From the viewpoint of forming a magnetic layer showing high magnetic permeability, the magnetic particles are preferably particles with a flat shape (flat particles), more preferably metal particles with a flat shape. By configuring the long side direction of the flat particles to be closer to parallel with the in-plane direction of the magnetic layer so that the long side direction of the particles is further consistent with the vibration direction of the electromagnetic wave orthogonally incident with respect to the electromagnetic wave shielding material, the diamagnetic field can be reduced, so the magnetic layer can show a higher magnetic permeability. In the present invention and this specification, "flat particles" refer to particles with an aspect ratio of less than 0.20. The aspect ratio of the flat particles is preferably less than 0.15, more preferably less than 0.10. The aspect ratio of the flat particles can be, for example, more than 0.01, more than 0.02 or more than 0.03. For example, by using a known method for flattening, the shape of the particles can be made into a flat shape. Regarding flattening, for example, reference can be made to the records of Japanese Patent Publication No. 2018-131640, for example, reference can be made to the records of paragraphs 0016 and 0017 of the publication and the embodiments. An example of a magnetic layer having a high magnetic permeability is a magnetic layer containing flat particles of Sendust.

[0067] As described above, from the viewpoint of forming a layer showing high magnetic permeability as a magnetic layer, it is preferred to arrange the long side direction of the flat particles to be closer to parallel with respect to the in-plane direction of the magnetic layer. From this point of view, the absolute value of the average value of the orientation angle of the flat particles relative to the surface of the magnetic layer and the dispersion of the orientation angle, that is, the orientation degree is preferably 30° or less, more preferably 25° or less, further preferably 20° or less, and further preferably 15° or less. The orientation degree can be, for example, 3° or more, 5° or more, or 10° or more, or it can be lower than the values ​​exemplified here. The method for controlling the orientation degree will be described later.

[0068] In the present invention and this specification, the aspect ratio of the magnetic particles and the above-mentioned orientation degree are obtained by the following method.

[0069] The cross section of the magnetic layer was exposed by a known method. A cross section image was acquired as a scanning electron microscope (SEM) image of a randomly selected region of the cross section. The imaging conditions were set to an acceleration voltage of 2 kV and a magnification of 1000 times, and the SEM image was obtained as a reflected electron image.

[0070] The cv2.imread() function of the image processing library OpenCV4 (manufactured by Intel Corporation) was used, the second independent variable was set to 0 and read out in grayscale, and the middle brightness of the high brightness part and the low brightness part was used as the boundary, and the binary image was obtained using the cv2.threshold() function. The white part (high brightness part) in the binary image was determined as the magnetic particle.

[0071] For the obtained binary image, the rotated circumscribed rectangle corresponding to each magnetic particle part is obtained by cv2.minAreaRect() function, and the long side length, short side length and rotation angle are obtained by using it as the return value of cv2.minAreaRect() function. When the total number of magnetic particles contained in the above binary image is obtained, particles in which only a part of the particles is included in the binary image are also included. For particles in which only a part of the particles is included in the binary image, the long side length, short side length and rotation angle are obtained for the part included in the binary image. The ratio of the short side length to the long side length (short side length / long side length) thus obtained is set as the aspect ratio of each magnetic particle. In the present invention and this specification, when the aspect ratio is less than 0.20 and the number of magnetic particles determined to be flat particles is more than 10% based on the number of the total number of magnetic particles contained in the above binary image, the magnetic layer is judged as a "magnetic layer containing flat particles as magnetic particles". Then, the “orientation angle” is obtained from the rotation angle obtained above as a rotation angle with respect to the horizontal plane (the surface of the magnetic layer).

[0072] The particles with an aspect ratio of 0.20 or less obtained in the binarized image are determined as flat particles. For the orientation angles of all flat particles contained in the binarized image, the absolute value of the average value (arithmetic mean) and the sum of the variance are obtained. The sum thus obtained is set as "degree of orientation". In addition, the coordinates of the circumscribed rectangle are calculated using the cv2.boxPoints() function, and the image obtained by superimposing the rotated circumscribed rectangle on the original image is produced by the cv2.drawContours() function, and the rotated circumscribed rectangle that is obviously misdetected is excluded from the calculation of the aspect ratio and the degree of orientation. In addition, the average value (arithmetic mean) of the aspect ratio of the particles determined as flat particles is set as the aspect ratio of the flat particles contained in the magnetic layer of the measurement object. The aspect ratio is less than 0.20, preferably less than 0.15, and more preferably less than 0.10. In addition, the above-mentioned aspect ratio can be, for example, more than 0.01, more than 0.02 or more than 0.03.

[0073] The content of the magnetic particles in the magnetic layer can be, for example, 50% by mass or more, 60% by mass or more, 70% by mass or more, or 80% by mass or more relative to the total mass of the magnetic layer, and can be, for example, less than 100% by mass, less than 99% by mass, less than 98% by mass, or less than 95% by mass. The magnetic layer can contain only one type of magnetic particles, or can contain two or more types of magnetic particles in any proportion. In the present invention and this specification, when a certain component contains two or more types, the content and content refer to the total content and total content of these components. The content of various components in the magnetic layer can be obtained by TG / DTA (Thermogravimetry / Differential Thermal Analysis: thermogravimetry-differential thermal analysis), using solvents to extract various components and other well-known methods. In addition, "TG / DTA" is generally referred to as thermogravimetric differential thermal analysis. When the composition of the magnetic layer forming composition used to form the magnetic layer is known, the content of various components in the magnetic layer can also be obtained based on the known composition.

[0074] In one embodiment, the magnetic layer may be an insulating layer. In the present invention and this specification, "insulating" means that the electrical conductivity is less than 1S (Siemens) / m. The electrical conductivity of a certain layer is calculated by the following formula based on the surface resistivity of the layer and the thickness of the layer. The electrical conductivity can be measured by a known method.

[0075] Electrical conductivity [S / m] = 1 / (surface resistivity [Ω] × thickness [m])

[0076] The inventors speculate that the fact that the magnetic layer is an insulating layer is preferred from the perspective that the electromagnetic wave shielding material can exert a higher electromagnetic wave shielding performance. From this point of view, the conductivity of the magnetic layer is preferably less than 1 S / m, more preferably less than 0.5 S / m, further preferably less than 0.1 S / m, and further preferably less than 0.05 S / m. The conductivity of the magnetic layer can be, for example, 1.0×10 -12 S / m or above or 1.0×10 -10 S / m and above.

[0077] (resin)

[0078] The magnetic layer is a layer containing magnetic particles and resin. The resin can act as a binder in the magnetic layer. The content of the resin in the magnetic layer can be, for example, 5% by mass or more relative to the total mass of the magnetic layer. From the perspective of further improving the moldability, it is preferably 10% by mass or more, and more preferably 15% by mass or more. In addition, the content of the resin in the magnetic layer can be, for example, 50% by mass or less relative to the total mass of the magnetic layer. From the perspective of improving the magnetic permeability of the magnetic layer, it is preferably 45% by mass or less, more preferably 40% by mass or less, further preferably 35% by mass or less, further preferably 30% by mass or less, and further preferably 25% by mass or less.

[0079] In the present invention and this specification, "resin" means polymer, and also includes rubber and elastomer. Polymer includes homopolymer and copolymer. Rubber includes natural rubber and synthetic rubber. And, elastomer is a polymer showing elastic deformation. As the resin contained in the magnetic layer, previously known thermoplastic resins, thermosetting resins, ultraviolet curable resins, radiation curable resins, rubber-based materials and elastomers can be cited. As specific examples, polyester resins, polyethylene resins, polyvinyl chloride resins, polyvinyl butyral resins, polyurethane resins, polyester urethane resins, cellulose resins, ABS (acrylonitrile-butadiene-styrene) resins, nitrile-butadiene rubbers, styrene-butadiene rubbers, epoxy resins, phenolic resins, amide resins, silicone resins, styrene elastomers, olefin elastomers, vinyl chloride elastomers, polyester elastomers, polyamide elastomers, polyurethane elastomers and acrylic elastomers can be cited. Among them, from the viewpoint of improving the moldability of electromagnetic wave shielding materials, preferred are resins containing carbamate bonds, such as polyurethane resins, polyester carbamate resins, and polyurethane elastomers. In the present invention and this specification, "resin containing carbamate bonds" refers to a resin containing one or more carbamate bonds (-NH-C(=0)0-) in one molecule. In addition, the type of resin contained in the magnetic layer can be determined, for example, by organic analysis such as thermal decomposition GC / MS (Gas Chromatography / Mass spectrometry) and Fourier transform infrared spectroscopy. For example, when isocyanate component residues and / or polyol component residues are observed by thermal decomposition GC / MS, it can be determined as a resin containing a carbamate bond.

[0080] The electromagnetic wave shielding material can be bent into any shape for use. If the magnetic layer breaks when the shielding material is bent, the shielding performance may be reduced at the break. Therefore, it is preferred that the magnetic layer has excellent fracture resistance and is not easily broken when bent. From the viewpoint of improving the fracture resistance of the magnetic layer, the magnetic layer is preferably a layer containing a resin having a glass transition temperature Tg of less than 0°C. In the present invention and this specification, the glass transition temperature Tg is obtained as the baseline shift starting temperature of the heat flow diagram when the temperature is increased based on the measurement results of the heat flow measurement measured using a differential scanning calorimeter. From the viewpoint of further improving the fracture resistance of the magnetic layer, the glass transition temperature Tg of the resin contained in the magnetic layer is more preferably -3°C or less, more preferably -5°C or less, and more preferably -10°C or less, -20°C or less, -30°C or less, and -40°C or less. In addition, the glass transition temperature Tg of the resin contained in the magnetic layer can be, for example, -100°C or more, -90°C or more, -80°C or more, -70°C or more, or -60°C or more. In one embodiment, the resin having a glass transition temperature within the above range may be a urethane bond-containing resin.

[0081] The magnetic layer may contain, in addition to the above-mentioned components, one or more known additives such as a curing agent, a dispersant, a stabilizer, and a coupling agent in any amount.

[0082] For example, as a curing agent, a compound having a crosslinking group can be cited. In the case where the curing agent is a compound having a crosslinking group, in the magnetic layer containing such a curing agent, the curing agent can be contained in the magnetic layer in the form of at least a part of the crosslinking group undergoing a crosslinking reaction. In the present invention and this specification, "crosslinking group" refers to a group capable of undergoing a crosslinking reaction, and as a specific example thereof, an isocyanate group can be cited. In addition, as a curing agent, a compound having more than 2 (for example, more than 2 and less than 4) crosslinking groups in one molecule is preferred, and as a specific example thereof, a polyfunctional isocyanate can be cited. A polyfunctional isocyanate is a compound having more than 2 isocyanate groups in one molecule, for example, a compound having more than 2 and less than 4 isocyanate groups in one molecule. In one embodiment, when the resin contained in the magnetic layer is set to 100 parts by mass, the magnetic layer can contain more than 5 parts by mass or more than 10 parts by mass of a polyfunctional isocyanate, preferably more than 15 parts by mass of a polyfunctional isocyanate. In one embodiment, the magnetic layer may contain 100 parts by mass or less or 40 parts by mass or less of a polyfunctional isocyanate when the resin contained in the magnetic layer is 100 parts by mass. From the viewpoint of producing a magnetic layer with a small Tanδ as described above, it is preferred to increase the content of the curing agent in the magnetic layer.

[0083] <Metal Layer>

[0084] The electromagnetic wave shielding material has a multilayer structure, and the multilayer structure includes the magnetic layer between two metal layers, that is, a magnetic layer whose loss tangent Tanδ under 1 Hz dynamic viscoelasticity measurement is less than 0.35 in the temperature range of 0°C to 70°C. The electromagnetic wave shielding material includes one or more such multilayer structures, and may also include two or more. That is, the electromagnetic wave shielding material includes at least two metal layers, and may also include three or more metal layers. The two or more metal layers included in the electromagnetic wave shielding material have the same composition and thickness in one embodiment, and different compositions and / or thicknesses in another embodiment. Moreover, in the case where the electromagnetic wave shielding material includes two or more magnetic layers, the two or more magnetic layers have the same composition and thickness in one embodiment, and different compositions and / or thicknesses in another embodiment. A specific example of the layer structure of the electromagnetic wave shielding material will be described later.

[0085] As the metal layer, a layer containing one or more metals selected from a group consisting of various pure metals and various alloys can be used. The metal layer can exert an attenuation effect in the shielding material. The larger the propagation constant, the greater the attenuation effect, and the larger the conductivity, the larger the propagation constant, so the metal layer preferably contains a metal element with high conductivity. From this point of view, the metal layer preferably contains pure metals of Ag, Cu, Au or Al, or an alloy with any of these as the main component. Pure metal is a metal composed of a single metal element and may contain trace impurities. Generally, a metal with a purity of more than 99.0% composed of a single metal element is called a pure metal. Purity is a mass basis. Regarding alloys, one or more metal elements or non-metallic elements are usually added to pure metals to adjust the composition to prevent corrosion, increase strength, etc. The main component in the alloy refers to the component with the highest ratio based on the mass basis, for example, it can be a component that accounts for more than 80.0 mass% (for example, less than 100 mass% or less than 99.8 mass%) in the alloy. From the viewpoint of economic efficiency, pure metal Cu or Al, or an alloy containing Cu or Al as a main component is preferred, and from the viewpoint of high electrical conductivity, pure metal Cu or an alloy containing Cu as a main component is more preferred.

[0086] The purity of the metal in the metal layer, that is, the content of the metal relative to the total mass of the metal layer can be 99.0% by mass or more, preferably 99.5% by mass or more, and more preferably 99.8% by mass or more. Unless otherwise specified, the content of the metal in the metal layer refers to the content of the mass basis. For example, as a metal layer, a pure metal or alloy processed into a sheet can be used. For example, as a metal layer, a commercially available metal foil or a metal foil made by a known method can be used. Regarding the pure metal of Cu, thin sheets (so-called copper foil) of various thicknesses are commercially available. For example, such copper foil can be used as a metal layer. Among the copper foils, there are electrolytic copper foils obtained by electroplating copper foil to be precipitated on the cathode, and rolled copper foils obtained by applying heat and pressure to the ingot to roll it very thinly. Any copper foil can be used as the metal layer of the above-mentioned electromagnetic wave shielding material. And, for example, Al also has thin sheets (so-called aluminum foils) of various thicknesses commercially available. For example, such aluminum foils can be used as a metal layer.

[0087] From the perspective of lightweight electromagnetic wave shielding materials, one or two (preferably two) of the two metal layers contained in the above-mentioned multilayer structure are preferably metal layers containing a metal selected from the group consisting of Al and Mg. This is because the values ​​obtained by dividing the specific gravity of Al and Mg by the conductivity (specific gravity / conductivity) are both small. The smaller the metal used, the lighter the electromagnetic wave shielding material that can exert high shielding performance. As values ​​calculated based on literature values, for example, the values ​​obtained by dividing the specific gravity of Cu, Al and Mg by the conductivity (specific gravity / conductivity) are as follows. Cu: 1.5×10 -7 m / S,Al:7.6×10 -8 m / S,Mg:7.6×10 -8m / S. According to the above values, it can be said that Al and Mg are preferred metals from the perspective of lightweight electromagnetic wave shielding materials. The metal layer comprising a metal selected from the group consisting of Al and Mg may include only one of Al and Mg in one embodiment, and may include both in another embodiment. From the perspective of lightweight electromagnetic wave shielding materials, one or two layers (preferably two layers) of the two metal layers included in the above-mentioned multilayer structure are more preferably a metal layer having a content of 80.0% by mass or more of the metal selected from the group consisting of Al and Mg, and more preferably a metal layer having a content of 90.0% by mass or more of the metal selected from the group consisting of Al and Mg. The metal layer containing at least Al in Al and Mg may be a metal layer having an Al content of 80.0% by mass or more, or may be a metal layer having an Al content of 90.0% by mass or more. The metal layer containing at least Mg in Al and Mg may be a metal layer having an Mg content of 80.0% by mass or more, or may be a metal layer having an Mg content of 90.0% by mass or more. The content of the metal selected from the group consisting of Al and Mg, the Al content, and the Mg content, for example, may be less than 100 mass % or less than 99.9 mass %. The content of the metal selected from the group consisting of Al and Mg, the Al content, and the Mg content, respectively, are the content ratios relative to the total mass of the metal layer.

[0088] In one embodiment, one or more of the above-mentioned metal layers can be metal layers with a Cu content of 80.0% by mass or more. The Cu content of the layer can be 90.0% by mass or more, and can be 99.9% by mass or less. In addition, in one embodiment, one or more of the above-mentioned metal layers can be metal layers with an Al content of 80.0% by mass or more. The Al content of the layer can be 90.0% by mass or more, and can be less than 100% by mass or 99.9% by mass or less. The Cu content and the Al content are the contents relative to the total mass of the metal layer, respectively. In one embodiment, the metal layers contained in the above-mentioned electromagnetic wave shielding material can all be metal layers with a Cu or Al content within the above-mentioned range.

[0089] <Specific example of layer structure>

[0090] As specific examples of the layer structure of the electromagnetic wave shielding material, the following examples can be given.

[0091] Example 1: "Metal layer / magnetic layer / metal layer"

[0092] Example 2: “metal layer / magnetic layer / metal layer / magnetic layer / metal layer”

[0093] Example 3: “metal layer / magnetic layer / metal layer / magnetic layer / metal layer / magnetic layer / metal layer”

[0094] In an electromagnetic wave shielding material having a multilayer structure including the above-mentioned magnetic layer between two metal layers, for example, as shown in Examples 2 and 3, a metal layer sandwiching a magnetic layer in a certain multilayer structure is also a metal layer sandwiching a magnetic layer in another multilayer structure. In the above-mentioned electromagnetic wave shielding material, the total number of multilayer structures including the above-mentioned magnetic layer between two metal layers can be, for example, 1 to 4. The total number of the above-mentioned multilayer structures is 1 in Example 1, 2 in Example 2, and 3 in Example 3. From the perspective of further improving the shielding performance of the electromagnetic wave shielding material, it is preferred that the total number of the above-mentioned multilayer structures is 2 or more (for example, 2, 3 or 4). In the above, the symbol " / " is used to include both the situation that the layer recorded on the left side of the symbol and the layer recorded on the right side are directly in contact without other layers and are indirectly stacked via one or more other layers. As a specific example of the above-mentioned other layers, the layer for bonding described later can be cited. The total number of magnetic layers (i.e., magnetic layers whose loss tangent Tanδ under 1 Hz dynamic viscoelasticity measurement is less than 0.35 in the temperature range of 0°C to 70°C) contained in the electromagnetic wave shielding material is one or more layers, and may be two or more layers, and, for example, may be four or less layers. On the other hand, the total number of metal layers contained in the electromagnetic wave shielding material is two or more layers, and, for example, may be two to five layers.

[0095] <Various thicknesses>

[0096] Regarding the thickness of the metal layer, from the perspective of the processability of the metal layer and the shielding performance of the electromagnetic wave shielding material, the thickness of each layer is preferably 4 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, further preferably 15 μm or more, further preferably 20 μm or more, and further preferably 25 μm or more. On the other hand, regarding the thickness of the metal layer, from the perspective of the processability of the metal layer, the thickness of each layer is preferably 100 μm or less, more preferably 50 μm or less, further preferably 45 μm or less, and further preferably 40 μm or less.

[0097] If the thickness of one of the two metal layers sandwiching the magnetic layer is set to T1, and the thickness of the other metal layer is set to T2, and T1 is greater than T2 (i.e., T1=T2 or T1>T2), then the thickness ratio of the two metal layers (T2 / T1) can be, for example, greater than 0.10. From the perspective of being able to exhibit higher shielding performance against magnetic field waves, it is preferably greater than 0.15, more preferably greater than 0.30, further preferably greater than 0.50, further preferably greater than 0.70, and further preferably greater than 0.80. From the perspective of being able to exhibit higher shielding performance against magnetic field waves, the smaller the difference between T1 and T2, the more preferred. The thickness ratio (T2 / T1) can be less than 1.00, or it can be 1.00 (i.e., T1=T2). In the case where the above-mentioned electromagnetic wave shielding material includes more than two multilayer structures having the above-mentioned magnetic layer between two metal layers, the above-mentioned records related to the thickness ratio (T2 / T1) can be applicable to at least one of the above-mentioned multilayer structures contained in the above-mentioned electromagnetic wave shielding material, and can also be applicable to more than two or all of them.

[0098] The shielding material can be bent into any shape according to the purpose. If the width of the bent portion (hereinafter referred to as "bend width") becomes wider when the shielding material is bent, the shape of the bent portion becomes a gentle curve shape, which is sometimes difficult to process into the target shape. From this point of view, the narrower the above-mentioned bending width is, the more preferred it is. The thicker the total thickness of the metal layer contained in the shielding material, the wider the above-mentioned bending width tends to be. From the viewpoint of narrowing the bending width of the shielding material, the total thickness of the metal layer contained in the above-mentioned electromagnetic wave shielding material is preferably 100μm or less, more preferably 90μm or less, further preferably 80μm or less, further preferably 70μm or less, further preferably 60μm or less, further preferably 50μm or less, and further preferably 40μm or less. The total thickness of the metal layer contained in the above-mentioned electromagnetic wave shielding material can be, for example, 8μm or more or 10μm or more.

[0099] Regarding the thickness of the magnetic layer, from the perspective of the shielding performance of the electromagnetic wave shielding material, the thickness of each layer can be, for example, 3 μm or more, preferably 10 μm or more, and more preferably 20 μm or more. And, from the perspective of the processability of the electromagnetic wave shielding material, the thickness of each magnetic layer can be, for example, 90 μm or less, preferably 70 μm or less, and more preferably 50 μm or less. In the case where the electromagnetic wave shielding material includes more than two magnetic layers, the total thickness of the magnetic layers included in the electromagnetic wave shielding material can be, for example, 6 μm or more, and, for example, can be 180 μm or less.

[0100] Furthermore, the total thickness of the shielding material may be, for example, 350 μm or less. From the viewpoint of narrowing the bending width, it is also preferred that the total thickness of the shielding material is thinner. From this point of view, the total thickness of the electromagnetic wave shielding material is preferably 300 μm or less, more preferably 250 μm or less. The total thickness of the electromagnetic wave shielding material may be, for example, 30 μm or more or 40 μm or more.

[0101] The thickness of each layer included in the electromagnetic shielding material is a value obtained by photographing a cross section exposed by a known method using a scanning electron microscope (SEM) and calculating the arithmetic average of thicknesses at five points randomly selected from the obtained SEM image.

[0102] <Method for producing electromagnetic wave shielding material>

[0103] (Magnetic Layer Formation Method)

[0104] Regarding the above-mentioned magnetic layer, for example, it can be prepared by drying the coating layer provided by coating the magnetic layer forming composition. The magnetic layer forming composition contains the components described above and can arbitrarily contain one or more solvents. As the solvent, various organic solvents can be cited, for example, ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, carbitol acetate and other acetate ester solvents, cellosolve, butyl carbitol and other carbitols, toluene, xylene and other aromatic hydrocarbon solvents, dimethylformamide, dimethylacetamide, N-methylpyrrolidone and other amide solvents, etc. It is possible to use a solvent or two or more solvents selected in consideration of the solubility of the components used in the preparation of the magnetic layer forming composition in any ratio. The solvent content of the magnetic layer forming composition is not particularly limited and can be determined by considering the coating properties of the magnetic layer forming composition.

[0105] The magnetic layer forming composition can be prepared by mixing the various components in any order or mixing them simultaneously. Furthermore, as required, a known dispersing machine such as a ball mill, a bead mill, a sand mill, a roller mill, etc. can be used for dispersion treatment, and / or a known stirring machine such as a vibration stirrer can be used for stirring treatment.

[0106] The magnetic layer-forming composition can be applied, for example, to a support. Application can be performed using a known coating device such as a knife coater or a die coater. Application can also be performed in a so-called roll-to-roll method or in a batch method.

[0107] As a support for coating the composition for forming a magnetic layer, for example, films of various resins such as polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide can be cited. For these resin films, reference can be made to paragraphs 0081 to 0086 of Japanese Patent Publication No. 2015-187260. As a support, a support whose surface (coated surface) is coated with the composition for forming a magnetic layer and subjected to a release treatment by a known method can be used. As one method of the release treatment, the formation of a release layer can be cited. For the release layer, reference can be made to paragraph 0084 of Japanese Patent Publication No. 2015-187260. In addition, as a support, a commercially available resin film that has been subjected to a release treatment can also be used. By using a support body whose coated surface has been subjected to a release treatment, the magnetic layer and the support body can be easily separated after film formation.

[0108] In one embodiment, the magnetic layer-forming composition can be directly applied onto the metal layer using the metal layer as a support. By directly applying the magnetic layer-forming composition onto the metal layer, the magnetic layer can be formed directly onto the metal layer without intervening other layers.

[0109] The coating layer formed by applying the magnetic layer forming composition can be dried by a known method such as heating or blowing hot air. The drying process can be performed, for example, under conditions that allow the solvent contained in the magnetic layer forming composition to volatilize. As an example, the drying process can be performed in a heated atmosphere at an atmosphere temperature of 80 to 150° C. for 1 minute to 2 hours.

[0110] Regarding the composition for forming a magnetic layer that contains a curing agent in addition to magnetic particles and a resin, the curing agent can refer to the above description. The curing treatment of the curing agent can be applied to the magnetic layer formed using the composition for forming a magnetic layer at any stage. As the curing treatment, heat treatment or light irradiation treatment can be performed according to the type of curing agent. For example, in the case where the curing treatment is a heat treatment, the heat treatment can be performed before the pressurization treatment described later in one embodiment, and can be performed after the pressurization treatment described later in another embodiment. According to the research of the present inventors, it was found that if the above-mentioned heat treatment is performed after the pressurization treatment, the magnetic permeability of the formed magnetic layer tends to increase. The above-mentioned heat treatment can be performed, for example, by keeping the magnetic layer before or after the pressurization treatment in an environment with an atmospheric temperature of 35°C or above (for example, 35°C or above and 150°C or below). The above-mentioned holding time can be set to 3 to 72 hours, for example.

[0111] The orientation degree of the flat particles described in the above can be controlled by the solvent type, solvent amount, liquid viscosity, coating thickness, etc. of the magnetic layer forming composition. For example, if the boiling point of the solvent is low, the value of the orientation degree tends to increase due to convection caused by drying. If the amount of solvent is small, the value of the orientation degree tends to increase due to physical interference between adjacent flat particles. On the other hand, if the liquid viscosity is low, the value of the orientation degree tends to decrease due to the rotation of the flat particles. If the coating thickness is thinned, the value of the orientation degree tends to decrease. In addition, performing the pressure treatment described later can help reduce the value of the orientation degree. By adjusting the above-mentioned various manufacturing conditions, the orientation degree of the flat particles can be controlled within the range described in the above.

[0112] (Pressure treatment of magnetic layer)

[0113] The magnetic layer can also be subjected to a pressure treatment after film formation. By subjecting the magnetic layer containing magnetic particles to a pressure treatment, the density of the magnetic particles in the magnetic layer can be increased, and a higher magnetic permeability can be obtained. In addition, the magnetic layer containing flat particles can be subjected to a pressure treatment to reduce the value of the orientation degree, and a higher magnetic permeability can be obtained.

[0114] The pressurization treatment can be performed by applying pressure in the thickness direction of the magnetic layer using a plate press, a roller press, or the like. The plate press can place the object to be pressed between two flat pressing plates arranged one above the other and apply pressure to the object by closing the two pressing plates together under mechanical or hydraulic pressure. The roller press can apply pressure by passing the object to be pressed between rotating pressing rollers arranged one above the other and applying mechanical or hydraulic pressure to the pressing rollers at this time, or by making the distance between the pressing rollers smaller than the thickness of the object to be pressed.

[0115] The pressure during the press treatment can be set arbitrarily. For example, in the case of a plate press, it is 1 to 50 N (Newton) / mm 2 In the case of a roller press, the linear pressure is, for example, 20 to 400 N / mm.

[0116] The pressing time can be set arbitrarily. When a plate press is used, the pressing time is, for example, 5 seconds to 4 hours. When a roller press is used, the pressing time can be controlled by the conveying speed of the object to be pressed, for example, the conveying speed is 10 cm / min to 200 m / min.

[0117] The material of the pressing plate and the pressing roller can be arbitrarily selected from metal, ceramic, plastic, rubber, and the like.

[0118] When performing the pressurization treatment, for example, the upper and lower pressing plates or one side pressing plates of the plate press, or one side roller of the upper and lower rollers of the roller press can be subjected to heat and pressure treatment. In the heat and pressure treatment, the magnetic layer can be softened by heating, thereby obtaining a high compression effect when pressure is applied. The temperature during heating can be set arbitrarily, for example, above 50°C and below 200°C. The temperature during the heating can be the internal temperature of the pressing plate or the roller. The temperature can be measured by a thermometer provided inside the pressing plate or the roller. In one embodiment, a heat treatment can be performed before or after the heat and pressure treatment as a curing treatment of the curing agent. Regarding the heat treatment, it is as described above.

[0119] After the plate press is heated and pressurized, the plate can be separated to remove the magnetic layer, for example, while the temperature of the plate is high. Alternatively, the plate can be cooled by water cooling, air cooling, etc. while maintaining the pressure, and then the plate can be separated to remove the magnetic layer.

[0120] In a roll press, the magnetic layer can be cooled by water cooling, air cooling, or the like immediately after pressurization.

[0121] The pressurization treatment may be repeated two or more times.

[0122] When the magnetic layer is formed on a release film, for example, the pressure treatment can be performed in a state where the magnetic layer is laminated on the release film. Alternatively, the pressure treatment can be performed as a single magnetic layer after the magnetic layer is peeled off from the release film.

[0123] (Lamination of metal layer and magnetic layer)

[0124] The adjacent metal layer and magnetic layer can be directly bonded together, for example, by applying pressure and heat to perform compression bonding. A plate press, a roller press, etc. can be used for compression bonding. During the compression bonding process, the contact between the magnetic layer and the surface of the metal layer is promoted by softening the magnetic layer, so that the two adjacent layers can be bonded. The pressure during compression bonding can be set arbitrarily. In the case of a plate press, for example, it is 1 to 50 N / mm 2 . In the case of a roller press, for example, the line pressure is 20 to 400 N / mm. The pressing time during crimping can be set arbitrarily. In the case of a plate press, for example, it is 5 seconds to 30 minutes. In the case of a roller press, it can be controlled by the conveying speed of the pressurized object, for example, the conveying speed is 10 cm / minute to 200 m / minute. The temperature during crimping can be selected arbitrarily, for example, above 50°C and below 200°C. The temperature during the above-mentioned crimping can be, for example, the internal temperature of the pressing plate or the roller.

[0125] The metal layer and the magnetic layer can be bonded together by interposing an adhesive layer and / or a bonding layer between the metal layer and the magnetic layer.

[0126] In the present invention and this specification, "adhesive layer" refers to a layer having a sticky surface at room temperature. Here, "room temperature" refers to 23°C. Regarding the adhesive layer, the room temperature described later also refers to 23°C. When the layer contacts the adherend, it adheres to the adherend through its adhesion. Tackiness usually refers to the property of exerting adhesive force in a short time after contacting the adherend with a very light force. In the present invention and this specification, the above-mentioned "having stickiness" refers to the result of No.1 to No.32 in the tilted ball adhesion test (measurement environment: temperature 23°C, relative humidity 50%) specified in JIS Z 0237:2009. In the case where other layers are stacked on the surface of the adhesive layer, for example, the surface of the adhesive layer exposed by peeling off the other layers can be provided for the above test. In the case where other layers are stacked on one surface and the other surface of the adhesive layer, the other layers on either surface side can be peeled off.

[0127] As the adhesive layer, an adhesive layer obtained by coating an adhesive layer-forming composition containing an adhesive such as an acrylic adhesive, a rubber adhesive, a silicone adhesive, or a urethane adhesive and processing the composition into a film shape can be used.

[0128] The adhesive layer-forming composition can be applied, for example, to a support. Application can be performed using a known coating device such as a knife coater or a die coater. Application can also be performed in a so-called roll-to-roll method or in a batch method.

[0129] As the support of the composition for forming the coating adhesive layer, for example, films of various resins such as acrylic acid, cyclic polyolefin, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc., such as polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polymethyl methacrylate (PMMA), etc., can be enumerated. As a support, the surface (coated surface) of the composition for forming the coating adhesive layer can be used through the support implemented by a known method through stripping treatment. As a mode of stripping treatment, the formation of a release layer can be enumerated. And, as a support, commercially available resin films that have been stripped can also be used. By using the support implemented by stripping treatment on the coated surface, the adhesive layer can be easily separated from the support after film formation.

[0130] The adhesive layer can be laminated on the surface of the metal layer or the magnetic layer by applying the adhesive layer-forming composition in which the binder is dissolved and / or dispersed in a solvent onto the metal layer or the magnetic layer and drying the composition.

[0131] Furthermore, by overlaying a film-like adhesive layer on the metal layer or the magnetic layer and applying pressure, the adhesive layer can be laminated on the surface of the metal layer or the magnetic layer.

[0132] In order to make an electromagnetic wave shielding material with an adhesive layer, an adhesive tape containing an adhesive layer can also be used. As an adhesive tape, a double-sided tape can be used. Double-sided tape is an adhesive tape with an adhesive layer configured on both sides of a support, and the adhesive layers on both sides can be sticky at room temperature. In addition, as an adhesive tape, an adhesive tape with an adhesive layer configured on one side of a support can also be used. As a support, for example, films, non-woven fabrics, and paper of various resins such as polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylic acid such as polycarbonate (PC), and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide can be cited. As an adhesive tape in which an adhesive layer is configured on one or both sides of a support, a commercial product can be used, and a double-sided tape made by a known method can also be used.

[0133] In the present invention and this specification, "adhesive layer" is a layer having no stickiness on the surface at room temperature, and refers to a layer that flows and follows the tiny bumps on the surface of the adherend by being pressed on the adherend in a heated state, and exerts adhesive force through an anchoring effect, or a layer that produces chemical bonds with the surface of the adherend through a chemical reaction by being pressed on the adherend in a heated state, thereby exerting adhesive force. The adhesive layer can soften and / or cause a chemical reaction by heating. The above-mentioned "no stickiness" means that the No. 1 ball does not stop in the inclined ball adhesion test (measurement environment: temperature 23°C, relative humidity 50%) specified in JIS Z 0237:2009. In the case where other layers are stacked on the surface of the adhesive layer, for example, the surface of the adhesive layer exposed by peeling off the other layers can be provided for the above-mentioned test. In the case where other layers are stacked on one surface and the other surface of the adhesive layer, the other layers on either surface side can be peeled off.

[0134] As bonding layer, can use film-like resin material.As resin material, can use thermoplastic resin and / or thermosetting resin.Thermoplastic resin has the softening property by heating, flows and follows the tiny concavo-convex on adherend surface by being pressed on adherend under heated state, and can bring into play bonding force based on anchoring effect, can keep bonding state by cooling afterwards.Thermosetting resin can cause chemical reaction by heating, can produce chemical reaction by heating under the state contacting with adherend, and produces chemical bonding with adherend surface, thereby brings into play bonding force.

[0135] Examples of thermoplastic resins include polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyvinyl acetate, polyurethane, polyvinyl alcohol, ethylene-vinyl acetate copolymer, styrene butadiene rubber, acrylonitrile butadiene rubber, silicone rubber, olefin elastomer (PP), styrene elastomer, ABS resin, polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), and the like.

[0136] Examples of the thermosetting resin include epoxy resins, phenol resins, melamine resins, thermosetting urethane resins, xylene resins, and thermosetting silicone resins.

[0137] The adhesive layer contains a polymer having the same main skeleton as the resin contained in the magnetic layer, thereby increasing the compatibility between the resin contained in the magnetic layer and the resin contained in the adhesive layer, which is preferred from the perspective of the adhesion between the magnetic layer and the adhesive layer. For example, it is preferred that the magnetic layer contains a polyurethane resin and the adhesive layer also contains a polyurethane resin.

[0138] The film-like resin material used as the adhesive layer may be a commercially available product or a film-like resin material produced by a known method.

[0139] In one embodiment, a resin or resin precursor dissolved and / or dispersed in a solvent is applied to the metal layer or the magnetic layer and cured by drying or polymerization, thereby laminating an adhesive layer made of a film-like resin material on the surface of the metal layer or the magnetic layer.

[0140] Alternatively, the film-like adhesive layer can be formed by applying a resin or a resin precursor dissolved and / or dispersed in a solvent onto a support, curing the resin or the resin precursor by drying or polymerization to form an adhesive layer, and then peeling the resin from the support.

[0141] By overlaying a film-like adhesive layer on the metal layer or the magnetic layer and applying pressure under heating, the adhesive layer can be laminated on the surface of the metal layer or the magnetic layer.

[0142] The metal layer and the magnetic layer can be bonded to each other via the adhesive layer by applying pressure under heating in a state where the magnetic layer as an adherend is superimposed on the adhesive layer of the metal layer having the adhesive layer laminated on the surface.

[0143] Alternatively, the metal layer as an adherend may be superimposed on the adhesive layer of the magnetic layer having the adhesive layer laminated on the surface thereof, and then pressed under heating to bond the metal layer to the magnetic layer via the adhesive layer.

[0144] Alternatively, an adhesive layer of a film-like resin material is disposed between the metal layer and the magnetic layer, and these are stacked and pressed under heating, so that the metal layer and the magnetic layer can be bonded together via the adhesive layer.

[0145] The pressurization under heating can be performed using a plate press, a roll press, or the like equipped with a heating mechanism.

[0146] Furthermore, as an example of the adhesive member, there is also a double-sided tape described in Japanese Patent Application Laid-Open No. 2003-20453 as a silicone-based substrate-free double-sided tape.

[0147] The conductivity of the conventional adhesive layer and bonding layer is extremely small compared to the metal layer, the magnetic permeability is extremely small compared to the above-mentioned magnetic layer, and the relative dielectric constant is only several times that of air, and the characteristic impedance and propagation constant are at the same level as those of air. Therefore, the use of conventional adhesive layers and / or bonding layers will not affect the shielding performance of the shielding material, or the effect is so small that it can be ignored. Regarding the adhesive layer and bonding layer, the thickness of each layer is not particularly limited, for example, it can be greater than 1 μm and less than 30 μm.

[0148] In one embodiment, the electromagnetic wave shielding material can be produced through one or more of the following steps. However, the method for producing the electromagnetic wave shielding material is not particularly limited.

[0149] The metal layer and the magnetic layer are bonded together using a bonding layer or an adhesive layer formed in a film shape.

[0150] The metal layer and the magnetic layer are bonded together by forming the magnetic layer with an adhesive layer or a bonding layer provided on the surface thereof and bonding the magnetic layer and the metal layer together via the adhesive layer or the bonding layer.

[0151] The metal layer and the magnetic layer are bonded together by forming a metal layer having an adhesive layer or a bonding layer provided on the surface thereof and bonding the metal layer and the magnetic layer together via the adhesive layer or the bonding layer.

[0152] The adhesive layer or bonding layer is directly coated on the surface of the metal layer or the magnetic layer.

[0153] The magnetic layer having the adhesive layer or bonding layer on the surface is formed by coating an adhesive layer or bonding layer on a release film, applying pressure to press it to the magnetic layer, or applying heat and pressure to press it to the magnetic layer, and then peeling off the release film.

[0154] An adhesive layer or bonding layer is coated on a release film, and after being pressed against the magnetic layer by applying pressure or pressed against the metal layer by applying heat and pressure, the release film is peeled off to form a metal layer having an adhesive layer or bonding layer on its surface.

[0155] The electromagnetic wave shielding material may be in any shape such as a film (or sheet). For example, the electromagnetic wave shielding material in a film shape may be bent into any shape and incorporated into an electronic component or electronic device.

[0156] [Electronic parts]

[0157] One aspect of the present invention relates to an electronic component comprising the above-mentioned electromagnetic wave shielding material. As the above-mentioned electronic component, various electronic components such as electronic components, semiconductor components, capacitors, coils, cables, etc. contained in electronic devices such as mobile phones, mobile information terminals, and medical devices can be cited. The above-mentioned electromagnetic wave shielding material can be bent into any shape according to the shape of the electronic component and arranged inside the electronic component, or can be arranged as a covering material covering the outside of the electronic component. Alternatively, it can be processed into a cylindrical shape and arranged as a covering material covering the outside of the cable.

[0158] [Electronic equipment]

[0159] One aspect of the present invention relates to an electronic device comprising the above-mentioned electromagnetic wave shielding material. As the above-mentioned electronic device, electronic devices such as mobile phones, mobile information terminals, medical devices, electronic devices comprising various electronic parts such as semiconductor elements, capacitors, coils, cables, and electronic devices in which electronic parts are mounted on circuit boards, etc. can be cited. The electronic device can include the above-mentioned electromagnetic wave shielding material as a component of the electronic parts contained in the device. In addition, the above-mentioned electromagnetic wave shielding material can be configured inside the electronic device as a component of the electronic device, or can be configured as a covering material covering the outside of the electronic device. Alternatively, it can be processed into a cylindrical shape and configured as a covering material covering the outside of a cable.

[0160] As an example of the use of the above-mentioned electromagnetic wave shielding material, there can be cited the use of semiconductor packages on printed substrates covered with shielding materials. For example, "Electromagnetic Wave Shielding Technology in Semiconductor Packages" (Toshiba review Vol. 67 No. 2 (2012) P. 8) discloses a method of obtaining a high shielding effect by electrically connecting the side through-holes at the end of the package substrate to the inner surface of the shielding material when covering the semiconductor package with a shielding material. In order to perform such wiring, the outermost layer on the electronic component side of the shielding material is preferably a metal layer. Regarding the above-mentioned electromagnetic wave shielding material, in one method, one or two outermost layers of the shielding material can be a metal layer, so it can be preferably used when performing wiring as described above.

[0161] Example

[0162] Hereinafter, the present invention will be described in more detail based on examples. However, the present invention is not limited to the embodiments shown in the examples.

[0163] [Resin of magnetic layer]

[0164] The resins of the magnetic layer shown in Table 1 are the following resins. In Table 1, polyurethane resin is indicated as "polyurethane", and polyester urethane resin is indicated as "polyester urethane".

[0165] The polyurethane resin having a glass transition temperature Tg of -50°C was Nipporan 5120 manufactured by TOSOH CORPORATION.

[0166] The polyester urethane resin having a glass transition temperature Tg of -30°C is UR-6100 manufactured by TOYOBO Co., Ltd.

[0167] The polyester urethane resin having a glass transition temperature Tg of -3°C is UR-3200 manufactured by TOYOBO Co., Ltd.

[0168] The polyester urethane resin having a glass transition temperature Tg of 23° C. is UR-8300 manufactured by TOYOBO Co., Ltd.

[0169] The glass transition temperatures of the resins shown in Table 1 are values ​​determined by the following method.

[0170] The same resin (granular or powdered sample) as that used in the preparation of the magnetic layer-forming composition (coating liquid) was placed in an aluminum sample pan, sealed with a punch, and heat flow measurement was performed under the following conditions using Q100 manufactured by TA Instruments as a differential scanning calorimeter. Based on the measurement results, the glass transition temperature of the resin was determined as the baseline shift starting temperature of the heat flow diagram when the temperature was increased.

[0171] (Measurement conditions)

[0172] Scanning temperature: -80.0℃~200.0℃

[0173] Heating rate: 10.0℃ / min

[0174] [Example 1]

[0175] <Preparation of Magnetic Layer-Forming Composition (Coating Liquid)>

[0176] Add to plastic bottles

[0177] Fe-Si-Al flat magnetic particles (Fe-Si-Al alloy MFS-SUH manufactured by MKT Corp., Ltd.): 12 g

[0178] Polyurethane resin (Nipporan 5120 manufactured by TOSOH CORPORATION, solid content concentration 30% by mass): 3.3 g

[0179] Polyfunctional isocyanate (Takenate D101E manufactured by Mitsui Chemicals, Inc., solid content concentration 75 mass %): 0.4 g

[0180] Cyclohexanone: 25g

[0181] The coating solution was prepared by mixing for 12 hours using a vibration stirrer. The content of magnetic particles relative to the total mass of the magnetic layer formed from the prepared magnetic layer-forming composition and the content of the polyfunctional isocyanate relative to 100 parts by mass of the resin were the values ​​shown in Table 1.

[0182] <Fabrication of Magnetic Layer>

[0183] (Film Formation of Magnetic Layer)

[0184] The coating liquid was applied to the release surface of a PET film (PET75-JOL manufactured by Nippa Corporation) that had undergone a release treatment using a knife coater with a coating gap of 300 μm, and dried in a drying device with an internal atmosphere temperature of 80° C. for 30 minutes, thereby forming a film-like magnetic layer on the above-mentioned PET film that had undergone a release treatment.

[0185] (Pressure treatment and heat treatment of magnetic layer)

[0186] The upper and lower plates of a plate press (mini test press manufactured by TOYO SEIKI CO., LTD.) were heated to 140°C (internal temperature of the platen), and the magnetic layer of the PET film peeled off was sandwiched between two 1 mm thick Teflon (registered trademark) sheets, and a pressure of 30 N / mm was applied. 2 The pressure was maintained for 10 minutes. After the upper and lower pressing plates were cooled to 50° C. (internal temperature of the pressing plates) while the pressure was maintained, the magnetic layer was removed from between the two Teflon (registered trademark) sheets.

[0187] Thereafter, the magnetic layer was heat treated in a drying device at an internal temperature of 60° C. for 48 hours to allow the polyurethane resin contained in the magnetic layer to undergo a crosslinking reaction with the polyfunctional isocyanate, thereby obtaining a magnetic layer. Samples for various evaluations described below were cut out from a portion of the obtained magnetic layer.

[0188] <Production of shielding materials>

[0189] The magnetic layer obtained as described above was used as the magnetic layer, and an aluminum foil with a thickness of 50 μm was used as the metal layer (in accordance with JIS H4160:2006 standard, alloy number 1N30 state code (1) O, Al content 99.3 mass% or more), and the five layers of "aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer)" were laminated together with a double-sided tape (NeoFix5S2 manufactured by NEION Film Coatings Corp.) with a thickness of 5 μm between each layer.

[0190] In this way, an electromagnetic wave shielding material of Example 1 was obtained. The shielding material of Example 1 has a two-layer structure of "aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer)".

[0191] <Measurement of Magnetic Permeability>

[0192] A sample with a size of 28 mm × 10 mm was cut out from the magnetic layer, and the magnetic permeability was measured using a magnetic permeability measuring device (per01 manufactured by KEYCOM Corp.), and the magnetic permeability was obtained as the real part (μ') of the complex relative magnetic permeability at a frequency of 3 MHz (measurement temperature: 25° C.). The magnetic permeability thus obtained is shown in Table 1 as "magnetic permeability before thermal aging".

[0193] After the measurement of the magnetic permeability before heat aging, the sample for measurement was placed in a high temperature atmosphere of 120°C for 1 day, and the magnetic permeability was obtained by the above method (measurement temperature: 25°C). The magnetic permeability thus obtained is shown in Table 1 as "magnetic permeability after heat aging". Table 1 also shows the change rate of the magnetic permeability before and after heat aging calculated by the following formula.

[0194] Change rate (%) = magnetic permeability after heating time / magnetic permeability before heating time × 100

[0195] <Measurement of electrical conductivity>

[0196] A cylindrical main electrode with a diameter of 30 mm was connected to the negative electrode side of a digital super insulation resistance meter (TR-811A manufactured by Takeda Riken Industry Co., Ltd.), and a ring electrode with an inner diameter of 40 mm and an outer diameter of 50 mm was connected to the positive electrode side. The main electrode and the ring electrode were set on the sample piece of the magnetic layer cut into a size of 60 mm × 60 mm, and a voltage of 25 V was applied to both electrodes to measure the surface resistivity of the magnetic layer alone. The conductivity of the magnetic layer was calculated based on the surface resistivity and the following formula. The calculated conductivity is 1.1×10 -2 S / m.

[0197] As the thickness, the thickness of the magnetic layer obtained by the following method was used.

[0198] Electrical conductivity [S / m] = 1 / (surface resistivity [Ω] × thickness [m])

[0199] <Acquisition of Shielding Material Cross-Section Image>

[0200] The cross-section processing for exposing the cross section of the shielding material was performed by the following method.

[0201] The shielding material cut into a size of 3 mm×3 mm was embedded in a resin, and a cross section of the shielding material was cut out using an ion milling device (IM4000PLUS manufactured by Hitachi High-Tech Corporation).

[0202] The cross section of the shielding material thus exposed was observed using a scanning electron microscope (SU8220 manufactured by Hitachi High-Tech Corporation) at an acceleration voltage of 2 kV and a magnification of 100 times to obtain a reflected electron image. From the obtained image, the thickness of each of the two magnetic layers, the thickness of each of the three metal layers, and the total thickness of the shielding material were measured at 5 locations based on the scale bar. The arithmetic average of each was taken as the thickness of each magnetic layer, the thickness of each metal layer, and the total thickness of the shielding material. The thickness of each magnetic layer was 30 μm, the thickness of each metal layer was 50 μm, and the total thickness of the shielding material was 230 μm.

[0203] <Acquisition of Magnetic Layer Cross-Section Image>

[0204] Similarly to the above, in the cross section of the shield material of Example 1 exposed by cross-section processing, the magnetic layer portion was observed using a scanning electron microscope (SU8220 manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 2 kV and a magnification of 1000 times to obtain a reflected electron image.

[0205] <Measurement of aspect ratio of magnetic particles and degree of orientation of flat particles>

[0206] Using the reflected electron image obtained in the above, the aspect ratio of the magnetic particles was calculated by the method described in the above, and the flat particles were determined based on the value of the aspect ratio. As described in the above, it was determined whether the magnetic layer contained flat particles as magnetic particles, and the result was that the magnetic layer contained flat particles. In addition, for the magnetic particles determined to be flat particles, the orientation degree was calculated by the method described in the above, and the result was 13°. In addition, the average value (arithmetic mean) of the aspect ratios of all particles determined to be flat particles was calculated as the aspect ratio of the flat particles contained in the magnetic layer. The aspect ratio calculated was 0.071.

[0207] <Tanδ of magnetic layer>

[0208] A sample for measurement with a size of 28 mm × 10 mm was cut out from the magnetic layer, and a dynamic viscoelasticity measurement device DMS6100 manufactured by Hitachi High-Tech Science Corporation was used as a dynamic viscoelasticity measurement device, and the dynamic viscoelasticity measurement was performed according to the measurement steps described above. Based on the obtained measurement results, the loss tangent Tanδ under the dynamic viscoelasticity measurement at 1 Hz was calculated. The maximum value of the loss tangent Tanδ in the temperature range of 0°C to 70°C is shown in Table 1. For all of Example 1 and the following examples and comparative examples, the minimum value of the loss tangent Tanδ of the magnetic layer under the dynamic viscoelasticity measurement at 1 Hz in the temperature range of 0°C to 70°C is 0.02 or more.

[0209] <Evaluation of shielding performance (KEC method)>

[0210] A shielding material cut into a size of 150 mm × 150 mm was set between the antennas of the KEC method evaluation device including a signal generator, an amplifier, a pair of magnetic field antennas and a spectrum analyzer, and the ratio of the received signal strength without the shielding material to the received signal strength with the shielding material at a frequency of 100 kHz was obtained as the shielding performance. This operation was performed on the magnetic field antenna to obtain the electromagnetic wave shielding performance (magnetic field wave shielding performance). In addition, KEC is the abbreviation of the Kansai Electronic Industry Promotion Center.

[0211] The above evaluation was performed before and after the shielding material was placed in a high temperature atmosphere of 120°C for 1 day. The shielding performance was evaluated according to the following evaluation criteria based on the values ​​obtained through each evaluation. The evaluation results obtained for the shielding material before being placed in the above high temperature atmosphere are shown in Table 1 as the evaluation results of "before heat time", and the results obtained for the shielding material after being placed in the above high temperature atmosphere are shown in Table 1 as the evaluation results of "after heat time".

[0212] (Evaluation Criteria)

[0213] A: 30dB or more

[0214] B: 25dB or more and less than 30dB

[0215] C: Less than 25dB

[0216] [Examples 2 to 4, Examples 7 to 9, Comparative Examples 1 and 2]

[0217] The electromagnetic shielding material was produced and various evaluations were performed by the method described in Example 1 except that the items shown in Table 1 were changed as shown in Table 1.

[0218] The thicknesses of the above-described examples and comparative examples were measured by the above-described methods. As a result, the thickness of each magnetic layer, the thickness of each aluminum foil (metal layer), and the total thickness of the shielding material were the same as those obtained in Example 1.

[0219] [Example 5]

[0220] The three layers of "aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer)" were bonded together with a 5 μm thick double-sided tape (NeoFix5 S2 manufactured by NEION Film Coatings Corp.) placed between the layers. Electromagnetic wave shielding materials were produced and various evaluations were performed by the method described in Example 3.

[0221] In this way, an electromagnetic wave shielding material of Example 5 was obtained. The shielding material of Example 5 has a multilayer structure of "aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer)".

[0222] In Example 5, various thicknesses were measured by the method described above. As a result, the thickness of the magnetic layer and the thickness of each aluminum foil (metal layer) were the same as those obtained in Example 1, and the total thickness of the shielding material was 140 μm.

[0223] [Example 6]

[0224] The electromagnetic shielding material was produced and evaluated in accordance with the method described in Example 1 except that a 35 μm thick copper foil (according to JIS H3100:2018, alloy number C1100R, Cu content 99.9 mass % or more) was used instead of the aluminum foil as the metal layer.

[0225] In this way, an electromagnetic shielding material of Example 6 was obtained. The shielding material of Example 6 has a two-layer structure of "copper foil (metal layer) / magnetic layer / copper foil (metal layer)".

[0226] In Example 6, various thicknesses were measured by the method described above. As a result, the thickness of each magnetic layer was 30 μm, the thickness of each metal layer was 35 μm, and the total thickness of the shielding material was 185 μm.

[0227] [Example 10]

[0228] Prior to the pressure treatment of the magnetic layer, the magnetic layer was heat-treated by being kept in a drying device at an internal atmosphere temperature of 60° C. for 48 hours in order to cause a cross-linking reaction between the polyurethane resin contained in the magnetic layer and the polyfunctional isocyanate. After the heat treatment, the magnetic layer was pressure-treated by the method described in Example 1, but heat treatment after the pressure treatment was not performed.

[0229] The electromagnetic wave shielding material was produced and various evaluations were performed by the method described in Example 1 except for the above-mentioned points.

[0230] In this way, an electromagnetic shielding material of Example 10 was obtained. The shielding material of Example 10 has a two-layer structure of "aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer)".

[0231] In Example 10, various thicknesses were measured by the method described above. As a result, the thickness of each magnetic layer was 30 μm, the thickness of each metal layer was 50 μm, and the total thickness of the shielding material was 230 μm.

[0232] [Comparative Example 3]

[0233] A magnetic layer and a 100 μm thick aluminum foil (according to JIS H4160:2006 standard, alloy number 1N30 state code (1) O, Al content 99.3 mass % or more) were bonded together with double-sided tape. In addition, the electromagnetic wave shielding material was produced and various evaluations were carried out by the method described in Example 1.

[0234] Thus, an electromagnetic shielding material of Comparative Example 3 was obtained. For Comparative Example 3, various thicknesses were measured by the above-described method. As a result, the thickness of the magnetic layer was 30 μm, the thickness of the metal layer was 100 μm, and the total thickness of the shielding material was 135 μm.

[0235] The above results are shown in Table 1. In Table 1, aluminum foil is abbreviated as "Al", copper foil is abbreviated as "Cu", and magnetic layer is abbreviated as "magnetic".

[0236]

[0237] Regarding Examples 1, 7, and 8 in which the glass transition temperature Tg of the resin contained in the magnetic layer is different, a sample piece of 20 cm × 20 cm size was cut out from the produced magnetic layer. The cut sample piece was bent in half by hand and then unfolded to make it flat. As a result, in Examples 1 and 7, no fracture was observed in the bent magnetic layer, while in Example 8, fracture was observed in the bent magnetic layer.

[0238] Industrial Applicability

[0239] One embodiment of the present invention is useful in the technical field of various electronic components and various electronic devices.

Claims

1. An electromagnetic wave shielding material having a magnetic layer containing magnetic particles and a resin between two metal layers, and The loss tangent Tanδ of the magnetic layer in a 1 Hz dynamic viscoelasticity measurement is less than 0.35 within a temperature range of 0°C to 70°C.

2. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains a resin containing a urethane bond.

3. The electromagnetic wave shielding material according to claim 1, wherein The glass transition temperature of the resin is not less than -60°C and less than 0°C.

4. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains a urethane bond-containing resin having a glass transition temperature of -60°C or higher and lower than 0°C.

5. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains a polyfunctional isocyanate.

6. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains 15 parts by mass or more of a polyfunctional isocyanate based on 100 parts by mass of the resin.

7. The electromagnetic wave shielding material according to claim 1, wherein The magnetic permeability of the magnetic layer is greater than 100.

8. The electromagnetic wave shielding material according to claim 1, wherein The electromagnetic wave shielding material includes two or more multilayer structures, wherein the multilayer structure has a magnetic layer between two metal layers, the loss tangent Tanδ of which is less than 0.35 in a temperature range of 0°C to 70°C under a 1 Hz dynamic viscoelasticity measurement.

9. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains a urethane bond-containing resin having a glass transition temperature of not less than -60°C and less than 0°C. The magnetic layer contains 15 parts by mass or more of a polyfunctional isocyanate when the content of the resin is 100 parts by mass. The magnetic permeability of the magnetic layer is greater than 100, and The electromagnetic wave shielding material includes two or more multilayer structures, wherein the multilayer structure has a magnetic layer between two metal layers, the loss tangent Tanδ of which is less than 0.35 in a temperature range of 0°C to 70°C under a 1 Hz dynamic viscoelasticity measurement. 10 . An electronic component comprising the electromagnetic wave shielding material according to claim 1 . 11 . An electronic device comprising the electromagnetic wave shielding material according to claim 1 .

Citation Information

Patent Citations

  • Silicon-based substrate-free double-coated tape and method for using the same tape

    JP2003020453A

  • Adhesive film

    JP2015187260A

  • Soft magnetic flat powder

    JP2018131640A

  • Soft magnetic film

    WO2014132880A1